2022
DOI: 10.1007/s11419-022-00634-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term storage temperatures and sodium fluoride preservation on the stability of synthetic cathinones and dihydro-metabolites in human whole blood

Abstract: Purpose Synthetic cathinones, one of the largest groups of new psychoactive substances, represent a large analytical and interpretative challenge in forensic laboratories. Of these is the synthetic cathinones’ instability in different biological samples, which may lead to drug concentration discrepancies when interpreting toxicological findings. In this study, the stability of a panel of synthetic cathinones and their dihydro-metabolites (n = 26) together with internal standard was monitored in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Considering the polarity and solubility distribution of NPSs, we chose 50% methanol as one of the solvents for drug stability evaluation. Some previous studies that investigated the stability of synthetic cathinones used preservatives or buffers containing metal ions for different pH solutions [ 14 , 28 ]. However, metal ions may interfere with mass spectrometry or damage the instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the polarity and solubility distribution of NPSs, we chose 50% methanol as one of the solvents for drug stability evaluation. Some previous studies that investigated the stability of synthetic cathinones used preservatives or buffers containing metal ions for different pH solutions [ 14 , 28 ]. However, metal ions may interfere with mass spectrometry or damage the instrument.…”
Section: Resultsmentioning
confidence: 99%
“…34 Folate demonstrated poor stability data for the tested serum separator tubes, gel-free serum, and lithium heparin plasma. 7 In the preliminary study of measuring 5-MTHF, we observed the instability of 5-MTHF, which may affect the detection results and interfere with clinical diagnosis of disease, 8 including hyperhomocysteinaemia, 9 neural tube defects, 10 congenital malformations, 11 autoimmune disease, 3 and so on.…”
Section: Introductionmentioning
confidence: 99%